Evaluation of Immunoprotective Activities of White Button Mushroom (Agaricus bisporus) Water Extract Against Major Pathogenic Bacteria (Aeromonas hydrophila or Vibrio fluvialis) in Goldfish (Carassius auratus) - Shujun Sun; Jing Chen; Pan Cui; Xiaoxiao Yang; Yuhan Zheng; Zijian Ma; Yong Liu; Xiang Liu (Animals)
The white button mushroom (Agaricus bisporus) is a widely cultivated edible and medicinal mushroom, which contains various active substances, and has application value against pathogenic bacteria in aquaculture. Firstly, A. bisporus water extract (AB-WE) was prepared. Through the detection kits, it was found that the polysaccharide, protein, and polyphenol components of AB-WE were 9.11%, 3.3%, and 1.5%, respectively. The 246 compounds were identified in AB-WE, and the major small-molecule components included L-Isoleucine, L-Tyrosine, L-Valine, and Linoleic acid by HPLC-Q Exactive-Orbitrap-MS. Secondly, the AB-WE was evaluated for its immunological activities through dietary administration and pathogen challenge (Aeromonas hydrophila and Vibrio fluvialis) in goldfish (Carassius auratus). The results showed that the levels of immune factors of acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM) increased (p < 0.05) in goldfish, and the relative percentage survival of AB-WE against A. hydrophila and V. fluvialis were 80.00% (p < 0.05) and 81.82% (p < 0.05), respectively. The AB-WE reduced the bacterial content in renal tissue, enhanced the phagocytic activity of leukocytes, and exhibited antioxidant and anti-inflammatory effects by reducing the expression of antioxidant-related factors and inflammatory factors. Through histopathological and immunofluorescence techniques, it was found that AB-WE maintained the integrity of visceral tissues and reduced renal tissue apoptosis and DNA damage. Therefore, AB-WE exhibits immunoprotective activity against A. hydrophila and V. fluvialis infections in fish, and holds promise as an immunotherapeutic agent against major pathogenic bacteria in aquaculture.